Validation of a fear test in sport horses using infrared thermography - Dai, F.; Cogi, N. H.; Heinzl, E. U. L.; Costa, E. D.; Canali, E.; Minero, M. (Journal of Veterinary Behavior Clinical Applications and Research, 2015)
The aims of the present study were to assess feasibility and validity of a fear test in adult sport horses and to investigate whether the exposure to a fearful stimulus induces a change in eye temperature. Fifty horses, aged 14 ± 6 years, of different breed and gender, entered the study. For each horse, a caretaker was asked to fill in a validated temperament questionnaire. A novel object fear test (NOT), has been selected from literature to examine fearfulness. Temperature of the lacrimal caruncle was measured before the test and after the test on 22 horses, representative of the whole sample. To assess discriminant validity of the NOT, 3 human-animal relationship tests were performed on the same horses. Data were analyzed with descriptive, nonparametric, and multivariate statistic methods. No significant differences were found between females and geldings for any of the measured variables. Horses that were described by caretakers as more prone to panic, vigilant, excitable, skittish, and nervous (P < 0.001) needed significantly longer time to reapproach the novel object (P < 0.01). Eye temperature was significantly higher after the NOT compared to basal (P < 0.01), with subjects who did not reapproach the novel object tending to present larger increases (P < 0.10). Horses showing more fear-related responses to the NOT did not show more negative reactions to humans during the human-animal tests. These results suggest that, to some extent, the NOT predicts horses' behavior in real on-farm situations. Our findings reject the hypothesis that reactivity to humans and general fearfulness belong to the same basic feature of temperament. Importantly, infrared thermography proved to be useful in assessing physiological reactions of fear in horses.